Credit Contagion from Counterparty Risk - JORION, PHILIPPE; ZHANG, GAIYAN (Journal of Finance, 2009)
Standard credit risk models cannot explain the observed clustering of default, sometimes described as “credit contagion.” This paper provides the first empirical analysis of credit contagion via direct counterparty effects. We find that bankruptcy announcements cause negative abnormal equity returns and increases in CDS spreads for creditors. In addition, creditors with large exposures are more likely to suffer from financial distress later. This suggests that counterparty risk is a potential additional channel of credit contagion. Indeed, the fear of counterparty defaults among financial institutions explains the sudden worsening of the credit crisis after the Lehman bankruptcy in September 2008.